Recent advances on antimicrobial wound dressing: A review - Simões, Déborah (2018)
Skin and soft tissue infections (SSTIs) have high rates of morbidity and mortality associated. Despite the successful treatment of some SSTIs, those affecting the subcutaneous tissue, fascia, or muscle delay the healing process and can lead to life-threatening conditions. Therefore, more effective treatments are required to deal with such pathological situations. Recently, wound dressings loaded with antimicrobial agents emerged as viable options to reduce wound bacterial colonization and infection, in order to improve the healing process. In this review, an overview of the most prominent antibacterial agents incorporated in wound dressings along with their mode of action is provided. Furthermore, the recent advances in the therapeutic approaches used in the clinic and some future perspectives regarding antibacterial wound dressings are also discussed.